1977
DOI: 10.1139/m77-213
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acetohydroxamic acid on experimental Corynebacterium renale pyelonephritis

Abstract: The role of Corynebacterium renale urease in the establishment of pyelonephritis was studied by the oral administration of acetohydroxamic acid (AHA), a urease inhibitor, to experimentally infected rats. The bacteria were introduced by surgical insertion of a zinc disc containing 1 X 10(6) colony-forming units of C-renale into the urinary bladder whereas sterile discs were implanted in the bladders of the control animals. Daily administration of AHA via the drinking water did not halt the development of pyelon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…However, the rats developed cystitis. This evidence suggests that the ammonia liberated from ureolysis causes the alkalinization of the urine and may account, in part, for the necrosis of kidney tissue associated with pyelonephritis (93,94).…”
Section: Role Of Urease In Pathogenesismentioning
confidence: 98%
See 2 more Smart Citations
“…However, the rats developed cystitis. This evidence suggests that the ammonia liberated from ureolysis causes the alkalinization of the urine and may account, in part, for the necrosis of kidney tissue associated with pyelonephritis (93,94).…”
Section: Role Of Urease In Pathogenesismentioning
confidence: 98%
“…Bovine pyelonephritis is caused by Corynebacterium renale (94), an organism that possesses an active urease. Infection with this microorganism resulted in alkaline urine, growth of Coryniebacteriiuin ren/ile from kidney homogenates and urine, and necrosis of the renal tissue (94).…”
Section: Role Of Urease In Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of urease has been suggested as a means of preventing these clinical conditions (8,11,16). However, despite the fact that bacterial ureases are responsible, much of the experimental work has been done with ureases from vegetable sources (3,7,17), since there appears to be a tacit assumption that "urease" is a single entity.…”
mentioning
confidence: 99%
“…In an attempt to facilitate the study of the pathogenesis of C. renale-induced pyelonephritis, a rat experimental model was developed (9), and it was shown that the gross appearance and histological condition of the renal tissue of infected rats bore a close resemblance to that of the renal tissue of cows exhibiting signs of pyelonephritis. In addition, experimental infection in rats could be prevented (10) by the daily oral administration of the urease inhibitor acetohydroxamic acid, and evidence was presented to indicate that the powerful urease possessed by C. renale (12,15) could play a role in the pathogenesis of this disease.…”
mentioning
confidence: 99%